Model reduction by moment matching at isolated singularities for linear systems: a complex analytic approach - Padoan,A; Astolfi,A (Elsevier, 2017)
The model reduction problem by moment matching for continuous-time, single-input, single-output, linear, time-invariant systems is studied at isolated singularities (in particular, at poles). The notion of moment at a pole of the transfer function is defined. Exploiting this notion a one-to-one correspondence between moments at a pole of the transfer function and the “limit solution” of a family of Sylvester equations is established. Finally, a family of reduced order models is defined. A simple example illustrates the theory.